Who are the prisoners? - Dores, A. (Crítica Penal y Poder, 2018)
Criminal proceedings are socially unequal. But are they discriminatory? The impunity of some corresponds, in fact, to the ruthless condemnation of others, including due to miscarriages of justice or for minor offenses. Sociology, without being able to be definitive as to whether or not there is organized discrimination and how, presents sociographic data of the prison population. A population that is impoverished, young, male, poorly educated. Psychology contributes with likely causes of predisposition to fulfil the role of prisoner: family disruption, school failure, exclusionary cultures. Practitioners on the ground recognize pre-offenders before the age of criminal responsibility. The police demand convictions from an early age, from experience, recognizing in them the new generation of criminals who will soon commit crimes of their own. Will the analytical model most used in social theory, separating the political, economic, social and cultural dimensions, be the most appropriate to explain what the social role of the prisoners might be? What happens to the people living in the negative side of these dimensions? There is a consensus about the influence of the economic situation on the likelihood of someone being incarcerated. But there is no agreement as to how institutional processes with such symbolic and political importance as the criminal courts accept being part of a socially selective process so admittedly unjust: how do these organs of sovereignty offer themselves to fulfill a purpose so patently opposed to their doctrinal aims, and how do they gain political legitimacy by doing so? How is it that they sometimes are used to incarcerate the politically or merely socially inconvenient among us? Given that we are in the presence of a global phenomenon (all states and all powers use sequestration as a form of social control) we ask ourselves whether the typical dimensions used by social theory serve the needs of understanding prisons. Is the social role of prisoners economic, political, cultural, of status? How does this explain the centrality of gender and stigma? How to, in practice, explain the normative inconsistencies and claims of the special dangerousness of young men? Why has torture in the prisons become an internationally recognized fact by the custodial states, to the point of they themselves recognizing their incompetence to abolish such prohibited and disgusting practices? Around the hypothesis that the bulk of prisoners are modern scapegoats unconsciously created by states, according to a traditional formula for appeasing feelings of vindictiveness, we discuss the explanatory relevance of this anthropological hypothesis to the study of prisons